Faktor-Faktor yang Berhubungan dengan Perilaku Personal hygiene Organ Genitalia pada Pelajar putri di SMK N 7 Surakarta - Lufiati, Deny Eva, Anisa Catur Wijayanti, S.K.M., M.Epid, Farid Setyo Nugroho, S.K.M (2015)
Personal Hygiene is the beginning of keeping reproductive health, it relates to the issue of reproductive tract infections functionally. Personal hygiene relates to the cleanness of the organ. Genitalia organ is important to take care as early as possible in order to avoid the disturbance or disease in the genitalia organ. The purpose of this research is to determine the factors related to personal hygiene genitalia organ behavior of the female student in SMK N 7 Surakarta. This study uses a cross-sectional design with observational. The population in this study was 505 students with a sample number is 211 students. The sample collecting uses proportional random sampling technique while the statistical test uses chi square test. The results show that there is a correlation between knowledge (p = 0.000), attitude (p = 0,000), family support (p =0,014) toward personal hygiene behavior of female student in SMK N 7 Surakarta.